Management of early mobilization in intensive care units: a multicenter cross-sectional study - Zhu Yan-Ping; Xia Li-Xia; Li Guo-Hong (Sciendo, 2018)
The aim of this study was to assess the management of early mobilization (EM) in Chinese intensive care units (ICUs).